New Histamine-Related Five-Membered N-Heterocycle Derivatives as Carbonic Anhydrase I Activators - Niccolò Chiaramonte; Alessio Gabellini; Andrea Angeli; Gianluca Bartolucci; Laura Braconi; Silvia Dei; Elisabetta Teodori; Claudiu T. Supuran; Maria Novella Romanelli (Molecules, 2022)
A series of histamine (HST)-related compounds were synthesized and tested for their activating properties on five physiologically relevant human Carbonic Anhydrase (hCA) isoforms (I, II, Va, VII and XIII). The imidazole ring of HST was replaced with different 5-membered heterocycles and the length of the aliphatic chain was varied. For the most interesting compounds some modifications on the terminal amino group were also performed. The most sensitive isoform to activation was hCA I (KA values in the low micromolar range), but surprisingly none of the new compounds displayed activity on hCA II. Some derivatives (1, 3a and 22) displayed an interesting selectivity for activating hCA I over hCA II, Va, VII and XIII.